Sliding Triboelectric Circular Motion Sensor with Real‐Time Hardware Processing. Issue 12 (6th August 2021) - Xie, Zhijie; Zeng, Zhenghui; Yang, Fei; Lv, Jingliang; Wang, Yu; Wu, Rensuan; Liu, Jiaxiu; Wang, Zhong Lin; Cheng, Tinghai
Abstract: Since circular motion becomes an important part of automated circulation equipment, a sliding triboelectric circular motion sensor (S‐TCMS) has been demonstrated to monitor the velocity and displacement of a circular motion. The S‐TCMS consists of the stator and slider, which is integrated with automated circular motion equipment for sensing applications. When the slider of PTFE grid slides between the stator's electrodes, four electrical signals are produced in the staggered electrode. The experimental results show that the voltage amplitude remains constant at different sliding velocities, showing good sensing stability. Also, this work proposes a real‐time hardware signal processing method, which converts the original S‐TCMS signal into two standard square wave signals. The method makes the sensing detection of S‐TCMS independent from electrostatic instrument and reduces the occupation of hardware resources. The sensing experimental results show that S‐TCMS can detect the velocity of circular motion with the maximum velocity deviation rate of less than 0.37%, the angular position sensing detection accuracy of 0.42°. The S‐TCMS shows good circular motion‐sensing characteristics after hardware signal processing. Abstract : The sliding triboelectric circular motion sensor (S‐TCMS) is proposed, which can monitor the velocity and displacement of a circular motion. Moreover, this work proposes a real‐time hardware signal processing method, which converts the original S‐TCMS signal into two standard square wave signals. The S‐TCMS shows good circular motion‐sensing characteristics after hardware signal processing.